Respuesta :

Answer:

the first one and that's the only one

2 Answers: Choice A and choice D

[tex]3i\sqrt{3} \ \text{ and } \ i\sqrt{27}[/tex]

===================================================

Work Shown:

We will use the rule that sqrt(A*B) = sqrt(A)*sqrt(B) to get the following

[tex]x = \sqrt{-27}\\\\x = \sqrt{-1*27}\\\\x = \sqrt{-1}*\sqrt{27}\\\\x = i\sqrt{27} \ \text{ ... one answer; choice D}\\\\x = i\sqrt{9*3}\\\\x = i\sqrt{9}*\sqrt{3}\\\\x = i*3*\sqrt{3}\\\\x = 3i\sqrt{3} \ \text{ ... another answer; choice A}\\\\[/tex]

While choices C and D seem to look equivalent, note how the 'i' is under the square root in choice C. The 'i' term must be outside the root to be equivalent to the original expression. We denote [tex]i=\sqrt{-1}[/tex]

ACCESS MORE